The impact of oil price fluctuations on the Algerian economy during the period 1990-2020- an econometric study using the Autoregressive Distributed Deceleration (ARDL) - Madjdoubi, Chahrazed; Affane, Aicha Zidelmel; Guessabi, Chaabane (The journal of contemporary issues in business and government, 2023)
This study aims to find out the extent of the impact of oil price fluctuations on the GDP in Algeria, through and using the autoregressive distributed lags (ARDL) model applied to annual time series for both GDP and oil prices from 1990 to 2022. Specifically, we found that there is a long-term equilibrium relationship between oil prices and the gross domestic product (GDP) , which means that the gross domestic product in Algeria is closely related to the changes in oil prices in the long run, and since this relationship is direct and significant, in the long run the volume of the gross domestic product increases. In Algeria, during periods when oil prices rise and vice versa in the case of decline, but in the short term there is a direct significant relationship between oil prices and GDP.